Aid to Sudan's Rebels: Right Idea, Wrong Plan - Lautze, Sue (Tufts Archival Research Center, 2005)
Terrorism, humanitarian and conflict-resolution issues keep Sudan a country of concern to US foreign policy makers. The amendment to the Foreign Operations Bill signed into law by President Clinton on November 29 permits the President to provide food assistance to rebel groups operating in Sudan. This policy shift signals a welcomed stance by the US indicating that the status quo in Sudan is no longer acceptable. It reflects a refreshing renewed commitment to engage with Sudanâs problems. However, its formulation is deeply flawed and its implementation is ill-advised.